Studi Pengaruh Kondisi Penyetelan Nosebar pada Mesin Kupas terhadap Tekanan Kempa dan Kualitas Potong Venir Study on the Influences of Nosebar Setting of a Peeler on the Compressive Forces and Cutting Quality of Veneer - Edi Suhaimi Bakar (Masyarakat Peneliti Kayu Indonesia, 2004)
For good cutting quality all peeling machines are always equipped with a nosebar. Position of the nosebar over the knife –determined by the gap and lead– is adjusted until it forms the knife-nosebar’s opening slightly smaller than the depth of cut. As the result, the compressive forces, which are important for controlling veneers’ depth of lathe checks, thickness deviation and surface roughness are imposed on the wood. In cutting forces analysis of many veneer-cutting studies, researchers are only able to analyze the characteristic of forces act at the knife, but the characteristic of forces at the nosebar and the compressive forces on wood has never been revealed. In this study the characteristic of the forces acting at the knife (Xc, Yc) and the nosebar (Xb, Yb), as well as the compressive force imposed on the wood are studied and discussed. It is also discussed the tripartite relationships between the nosebar setting, the compressive force, and cutting quality.